Análise da deformação pós-Rifte na Bacia do Araripe, Nordeste do Brasil - Almeida, Camila de (2010)
The Araripe Basin is located over Precambrian terrains of the Borborema Province, being part of Northeast Brazil inner basins. Its origin is related to the fragmentation of the Gondwana supercontinent and consequently opening of South Atlantic during early Cretaceous. The basin has a sedimentary infill encompassing four distinct evolution stages, comprising Paleozoic syneclisis, pre-rift, rift and post-rift. The target of this study comprises the post-rift section of the basin focusing deformational styles which affect evaporates from Ipubi Member of the Santana Formation, which is composed by gypsum and anidrite layers interbedded with shales. These units occur widespread across the basin. In the central part of the basin, near Nova Olinda-Santana do Cariri, evaporites are affected by an essentialy brittle deformation tipified by fibrous gypsum filled fractures, cutting massive layers of gypsum and anidrite. Veins with variable orientations and dips are observed in the region distributed over three main populations: i) a dominant NWSE with shallow to moderate NE dipping population, consisting of gypsum filled veins in which fibers are normal to vein walls; i) NE-SW veins with moderate SE dips containing subhorizontal growth fibers; and iii) N-S veins with shallow E-W dips with fibers oblique to vein walls. In the west portion of the basin, near Trindade-Ipubi-Araripina towns, evaporate layers are dominantly constituted by gypsum/anidrite finely stratified, showing a minor density of veins. These layers are affected by a unique style of deformation, more ductile, typified by gentle to open horizontal normal folding with several tens of meters length and with double plunging NW-SE or NE-SW hinges, configuring domic features. In detail, gypsum/anidrite laminae are affected by metre to decimeter scale close to tight folding, usually kinked, with broken hinges, locally turning into box folds. Veins show NE-SW main directions with shallow NE dips, growth fibers are parallel to vein walls, constituting slickenfibers. This region is marked by faults that affect Araripina Formation with NW-SE, NE-SW and E-W directions. The main structural styles and general orientations of structures which affected the post-rift section of Araripe Basin yielded important kinematic information analysis which led us to infer a E-W to NE-SW extension direction to the northeastern part of the Basin, whereas in the southeastern part, extension occurred in N-S direction. Thus, it was possible to determine a regional kinematic setting, through this analysis, characterizing a NE-SW to ENE-WSW system for the post-rift section, which is compatible with the tension settings for the Sout American Plate since Albian. Local variations at the fluid pressure linked (or not) to sedimentary overload variation define local tension settings. This way, at the northeastern portion of the basin, the post-rift deformation was governed by a setting which σ 1 is sub-horizontal trending NE-SW and, σ 3 is sub-vertical, emphasizing a reverse fault situation. At the southwestern portion however there was characterized a strike slip fault setting, featuring σ 1 trending ENEWSW and σ3 trending NNW-SSE